Total bacterial counts, enumeration (MPN) of coliform organisms and Escherichia coli on samples of meat retail. Cuts and boning equipamentin supermakets - Martinelli Filho, Alcides; Graner, Murilo; Barbin, Décio; Silveira, Expedito T. F. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
Total bacterial counts (32°C and 5°C) and most probable numbers (MPN) of coliform organisms and E. coli were determined for samples of three retail bovine meat cuts and cutting and boning equipment three supermarkets. In the oldest of these, total counts were higher on meat cuts prepared in the cutting room than on meat boned in the packing plant. Total counts were generally high on the equipment (higher for incubation at 32°C), with the wooden surfaces (tables, cutting boards) showing significaitly higher numbers than the metallic ones (eletric saw, knives). No differences could be found between counts on "clean" equipment and counts on equipment being-used. Coliform organisms were generally present; when meat samples were tested for this group of bacteria and for E. coli, it was found that 96% of the samples were positive for both.